Oxidation of 2-(2-Methoxyethoxy)ethanol and 2-(2-Ethoxyethoxy)ethanol by Diperiodatocuprate(III) in Alkaline Medium-A Kinetic and Mechanistic Study - Shan, Jinhuan; Li, Yi; Yin, Caihong; Bian, Gang (Asian Journal of Chemistry, 2013)
The kinetics of oxidation of 2-(2-methoxyethoxy)ethanol and 2-(2-ethoxyethoxy)ethanol by diperiodatocuprate(III) (DPC) in alkaline liquids had been investigated spectrophotometrically in the temperature range of 20 ºC to 40 ºC. It was found that the reaction was pseudo-first order in [DPC] and 1 < nap < 2 in the concentration of reductants. The pseudo-first order rate constant kobs decreased rapidly with an increase in [OH–] to a certain value, then increasing with the continuous increase in [OH–]. In addition, the kobs decreased with an increase in [IO4–]. There was no salt effect. The rate of 2-(2-ethoxyethoxy)ethanol was higher than 2-(2-methoxyethoxy)ethanol in stronger alkaline medium. A plausible mechanism involving pre-equilibriums before the rate controlling step and a free radical mechanism was proposed from the kinetics study. The rate equations derived from mechanism can explain all experimental phenomena. Moreover, the activation parameters at 298.2 K along with rate constants of the rate-determining step were calculated.